2007
DOI: 10.1126/science.1141374
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Low Rigidity of the Earth's Inner Core

Abstract: Earth's solid-iron inner core has a low rigidity that manifests itself in the anomalously low velocities of shear waves as compared to shear wave velocities measured in iron alloys. Normally, when estimating the elastic properties of a polycrystal, one calculates an average over different orientations of a single crystal. This approach does not take into account the grain boundaries and defects that are likely to be abundant at high temperatures relevant for the inner core conditions. By using molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
64
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 26 publications
9
64
1
Order By: Relevance
“…For example, it allows one to reproduce the structure of liquid iron [14]- [16] as well as its viscosity [7,17]. It also allows one to explain a number of features of IC [9,10]. The melting temperature of Fe at the pressure of the outer core-inner core boundary (330 GPa), according to the EAM, is consistent with the temperature computed from first principles [18] (later revised to a somewhat lower temperature) within the mutual error bars.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…For example, it allows one to reproduce the structure of liquid iron [14]- [16] as well as its viscosity [7,17]. It also allows one to explain a number of features of IC [9,10]. The melting temperature of Fe at the pressure of the outer core-inner core boundary (330 GPa), according to the EAM, is consistent with the temperature computed from first principles [18] (later revised to a somewhat lower temperature) within the mutual error bars.…”
supporting
confidence: 62%
“…It was suggested, on the basis of non-empirical [6] molecular dynamics (MD) simulations, that under high pressure iron transforms on heating to the body-centered cubic (bcc) phase [7]. A number of IC properties can be explained within the paradigm of the bcc iron phase stability under the IC PT conditions, such as the low shear modulus [8,9] and elastic anisotropy [10]. However, computations performed by Vocadlo et al [11] have not confirmed the bcc stability.…”
mentioning
confidence: 99%
“…The time step was equal to 0.5 fs. The bcc elastic constants have been computed earlier (54). The hcp elastic constants have been calculated in the present work in a way similar to the approach applied by L. Vočadlo (55).…”
Section: Modelmentioning
confidence: 99%
“…It is known that the resistance of pure iron to shear does not match the very low shear modulus of the Earth's inner core [4]. At 360 GPa pressure, Belonoshko et al calculated G=274.3 GPa at T =6000 K, and G=243.1…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted, that iron is its main component, however there is no consensus about the crystal phase in which iron is present. In recent years, Fe was suggested to occur in the core in the body-centered cubic (bcc) phase [1,2,3,4,5]. It is known, however, that the density of pure Fe is larger than that of the inner core.…”
Section: Introductionmentioning
confidence: 99%